Common millet and soybean intercropping with bio-fertilizer as sustainable practice for managing grain yield and quality - Šenk, Milena; Simić, Milena; Milojković-Opsenica, Dušanka; Brankov, Milan; Tolimir, Miodrag; Kodranov, Igor; Dragičević, Vesna (Frontiers in Nutrition, 2023)
Climate changes are one of the biggest threats for food security. Sustainable agriculture, focused on eco-friendly practices for highly efficient food production, enables greater resilience and safety. This study experimented on intercropping and bio-fertilizer application as convenient ecological solution for crop yield stability and quality. The experiment was conducted during 2018 and 2020 with soybean and common millet sown in three sowing patterns: alternating rows, alternating strips 1 (2 rows of soybean + 2 rows of millet) and alternating strips 2 (2 rows of soybean + 4 rows of millet), as well as sole crops (control), with or without a bio-fertilizer Coveron. Grain yield and nutrient grain yield response were calculated through land equivalent ratio (LER) and element-LER, while quality was estimated based on the concentration of antioxidants (phytate phosphorus, total phenolic compounds, and yellow pigment) and elements in grains, including potential bio-availability of essential elements. Results revealed LER values >1 for all sowing patterns, with the highest one achieved in alternating strips 1 (1.38) together with greater level of all antioxidants in millet grain. Intercropping significantly enhanced Fe and Mn accumulation in both crops, and simultaneously decreased concentration of potentially toxic elements (Al, Cr) in millet grain. Potential bio-availability of essential elements, expressed through ratio between phytic acid and Ca, Mg, Fe, and Zn, revealed smaller values in intercropped soybean as well as in millet with the bio-fertilizer. The bio-fertilizer also increased concentration of some micro-elements in millet grain, classifying it as high dependent plant to microbial inoculation. Interaction of intercropping and bio-fertilizer was most pronounced for LER, E-LER and accumulation of Fe and Mn in grains. These results highlighted the benefits of soybean-common millet intercropping, especially in combination with the bio-fertilizer, in a light of enhanced land utilization and nutrients absorption, thus increasing resilience of soybean and millet under dry-land conditions and low-input system toward stability and food security.